Visual Hierarchy Employed in Learning Videos: Gender Preferences - Marisa Yoestara; Nyak Mutia Ismail (Universitas Serambi Mekkah, 2022)
This research aimed to discover how male and female students used visual hierarchy in their learning videos. There were 7 female students and 6 male students from the English Department, Education, and Teacher Training Faculty engaged in this study. This study used a visual content analysis design and is qualitative in nature. The instruments used were 13 videos produced by the respondents containing teaching material for speaking class. The data collection was carried out through identifying, classifying, verifying, and generating meanings of the visual elements by peering into the visual elements embedded into the video such as style or shape, color, line, space, and scale to create and convey meaning intended. The data were later analyzed using interactive analysis by classifying out the irrelevant data, then displaying the data, to be later verifying them theoretically. The results reveal that, for female students, the style used was generally bright-colored animated visuals with varied textures such as furry animals or glossy cute ladies. The space is rather crowded and the object composition is mostly occupied on the right or left with standard scaling. Lines were used with varied width and weights. For male students, more natural style was engaged, muted colors without the implementation of lines and textures. The spacing is also plain, the object composition is centered, and the scaling is small, no lines were employed. It implies that female students engaged various visual elements in video editing compared to male students. Keywords: Visual, Hierarchy Analysis, Learning Video, Gender Preferences, Design in ELT